Public Debt around the World: A New Dataset of Central Government Debt - Dany Jaimovich; Ugo Panizza (Inter-American Development Bank, Research Department, 2006)
Commonly used datasets on the level of public debt provide incomplete country and period coverage. This paper presents a new dataset that includes complete series of central government debt for 89 countries over the 1991-2005 period and for seven other countries for the 1993-2005 period. The data set can be found at: http://www. iadb. org/res/pub_desc. cfm?pub_id=DBA-005
Keywords: 330; Öffentliche Schulden; Schuldenmanagement; Vergleich; Welt